Physicochemical and structural properties of starches from non-traditional sources in China - Yang Jingyi; Chagam Koteswara Reddy; Zhili Fan; Baojun Xu (Food Science and Human Wellness)
In this study, we isolated starches from non-traditional sources, including quinoa, lentil, arrowhead, gorgon fruit, sorghum, chickpea, proso millet, and purple potato and investigated their morphology, physicochemical, and functional properties. Significant differences in starch particle morphology, swelling power, solubility, syneresis, crystalline pattern, and pasting viscosity were observed among the starches from these non-traditional sources. Further, all these isolated starches had unique properties because of their characteristic distinct granules when seen under scanning electron microscopy (SEM). The amylose content of the isolated starches shown significant difference (P < 0.05), and the values ranged between 11.46 % and 37.61 %. Results demonstrated that the isolated starches contained between 79.82 % to 86.56 % starch, indicating that the isolated starches had high purity. X-ray diffraction (XRD) patterns of starches isolated from sorghum, proso millet, quinoa, purple potato, and gorgon fruit presented A-type diffraction pattern; while lentil seeds, arrowhead, and chickpea starches presented C-type diffraction pattern. Overall, these results will promote the development of products based on starch isolated from non-traditional starches.